Classroom Activities as Measure of Academic Performance of Senior Secondary School Students in Core Science Subjects - Omodara, M.F; Kolawole, E.B; Oluwatayo, J.A (Richtmann Publishing, 2013)
The study investigated classroom activities as measure of academic performance of senior secondary school students in corescience subjects. Participants were 54 science teachers and 1,620 SS2 students selected from the Schools across the 16 localGovernment Areas of Ekiti State using purposive and stratified random sampling techniques. Data were collected using a 28-item interaction schedule and achievement tests in biology, chemistry and physics constructed and administered by the EkitiState Ministry of Education. The data collected were analyzed using correlation and regression analyses. The findingsrevealed that there existed significant relationship between students’ participation in class lessons and their academicperformance, the relationship between the teachers activities in science lessons and the students’ Academic performance wassignificant, positive and very high. The classroom activities in science lessons accounted for 94.5% of the variability instudents’ academic performance.